Information, Trading, and Volatility: Evidence from Weather‐Sensitive Markets - FLEMING, JEFF; KIRBY, CHRIS; OSTDIEK, BARBARA (Journal of Finance, 2006)
ABSTRACT We find that trading‐ versus nontrading‐period variance ratios in weather‐sensitive markets are lower than those in the equity market and higher than those in the currency market. The variance ratios are also substantially lower during periods of the year when prices are most sensitive to the weather. Moreover, the comovement of returns and volatilities for related commodities is stronger during the weather‐sensitive season, largely due to stronger comovement during nontrading periods. These results are consistent with a strong link between prices and public information flow and cannot be explained by pricing errors or changes in trading activity.